The Southern Patagonian Andes: The Largest Mountain Ice Cap of the Southern Hemisphere - Mazzoni, Elizabeth; Coronato, Andrea Maria Josefa; Rabassa, Jorge Oscar
This chapter describes physiographic characteristics and geomorphological processes of the southernmost portion of the Andean Cordillera. This sector of the Andean Ranges includes the only two mountain ice fields of South America which represent the largest freshwater reserve of southern Patagonia. Discharge glaciers flow out of the ice fields on both sides, modeling the landscape in the past and present times. As a product of intense glacial action, the mountain ranges show steep slopes and rugged summits with cirque glaciers. The valleys are partially occupied by lakes, some of them of large size (over 1,000 km2). These basins are surrounded by basaltic tablelands, complex moraine systems, and glaciofluvial plains. The dominant geomorphological processes are glacial and fluvial, besides mass movements and cryogenic activity in the highest zone. The landscape is covered by several vegetation formations, adapted to the very important W–E rainfall gradient. This orographic system offers a landscape of great beauty and high biodiversity, protected within large national parks both in Argentina and Chile. Fil: Mazzoni, Elizabeth. Universidad Nacional de la Patagonia Austral; Argentina Fil: Coronato, Andrea Maria Josefa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Rabassa, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina